FROM COMPLICIT JOURNALISM TO MILITANT JOURNALISM: Politicians as media critics and strategic news users in contested political scenarios - Orchard, Ximena; Fergnani, Mario (Brazilian journalism research, 2024)
ABSTRACT – In this article we identify how critical discourses about the media and journalists are articulated on social media by political actors. We also analyze how such expressions of media criticism coexist with other strategic uses of news content in politicians’ social media repertoires. The argument is based on a qualitative analysis of media-related Twitter posts (N=2062), from the 50 most active politicians’ Twitter accounts in the month following the Chilean social uprising of October 2019. Our findings reveal that criticism of journalism came from both ends of the political spectrum, despite news about the protests being regularly shared and used as factual support for informing followers, position-taking, criticizing adversaries, and self-promotion. We discuss how these forms of politicians’ interactions with the news operate as challenges to the authority of journalistic work. RESUMO – Neste artigo identificamos como os atores políticos articulam discursos críticos sobre a mídia e os jornalistas nas redes sociais, e como tais expressões de crítica da mídia coexistem com usos estratégicos de conteúdos noticiosos nos repertórios de mídia social dos políticos. O argumento baseia-se numa análise qualitativa de mensagens publicadas (N=2062), pelas 50 contas mais ativas de políticos no Twitter no mês seguinte à revolta social chilena de outubro de 2019. As nossas conclusões revelam que as críticas ao jornalismo vieram de ambos os extremos do espectro político, apesar de as notícias sobre os protestos terem sido regularmente partilhadas e utilizadas como apoio factual para informar os seguidores, tomada de posição, crítica aos adversários e autopromoção. Discutimos como estas formas de interação dos políticos com as notícias operam como desafios à autoridade do trabalho jornalístico. RESUMEN – En este artículo identificamos cómo los actores políticos articulan discursos críticos sobre los medios y los periodistas en redes sociales, y cómo estas expresiones de crítica coexisten con usos estratégicos de las noticias en sus repertorios de redes sociales. El argumento se basa en un análisis cualitativo de mensajes (N=2062), publicados por las 50 cuentas de Twitter de políticos más activas en el mes posterior al estallido social chileno de octubre de 2019. Nuestros hallazgos revelan que las críticas al periodismo provinieron de ambos extremos del espectro político, a pesar de que las noticias sobre las protestas se compartieran regularmente y se usaran como apoyo factual para informar seguidores, para la toma de posiciones, la crítica a los adversarios y la autopromoción. Discutimos cómo estas formas de interacción de los políticos con las noticias operan como desafíos a la autoridad del trabajo periodístico.